MAQASHID SYARIAH AS AN ALTERNATIVE FRAMEWORK FOR A SUSTAINABLE STRATEGY FOR THE ECONOMIC TRANSFORMATION OF LOCAL COMMUNITIES - Jamudi; Abdul Naser Hasibuan; Sarmiana Batubara (RADJA PUBLIKA, 2026)
Land conversion as part of development transformation is fundamentally intended to promote economic growth and regional modernization; however, in practice, it often generates socio-economic and environmental conflicts within local communities. The increasing rate of land conversion has not always been accompanied by improved community welfare, but instead has led to the loss of agricultural labor opportunities, widening economic inequality, marginalization of local communities, domination by external business actors, and environmental degradation. This study aims to analyze the sustainability of local community economic transformation resulting from land conversion based on the Maqashid Syariah approach and to determine priority strategies using the Analytic Network Process (ANP) method. The research employs a mixed-methods approach using primary data collected through interviews, field observations, and pairwise comparison questionnaires involving experts and stakeholders. The findings reveal that the loss of agricultural labor employment, increasing economic inequality, and the dominance of external business actors are the main issues affecting local economic transformation. The priority strategy identified is inclusive community-based economic empowerment, supported by a strong level of respondent agreement (Kendall’s W = 0.824; p-value < 0.01), which aligns with the maqashid sharia principles of protecting wealth, life, and intellect.